Analysis of the Determination of Standard and Actual Raw Material Cost Calculations at PT Cipta Frima - Moh. Nasrul Setiawan Adam (CV. Media Digital Publikasi Indonesia, 2024)
This study aims to evaluate whether Cipta Frima Jaya company uses standard and actual costing in its activities, and whether it affects the company's profitability. Using a descriptive approach, this research will analyze the implementation and influence of standard and actual costs on the company's operations. The descriptive method in this study will include data collection related to standard and actual costing carried out by the company. The data may include information on how standard costs are set, how actual costs are monitored and recorded, and how comparisons between standard and actual costs are made. The analysis process will involve a comparison between standard and actual costs to evaluate the extent to which Cipta Frima Jaya company implements effective cost control practices. If there is a significant difference between standard and actual costs, the cause and impact on the company's profitability will be analyzed. The results of the analysis will provide an understanding of the effectiveness of standard and actual costing in controlling the company's production costs, as well as its impact on the company's overall financial performance. This information can be the basis for recommendations for improvement or improvement in cost management and decision making at Cipta Frima Jaya company. For the purpose of support PT Cipta Frima Jaya in these three areas, this research may subsequently be used for analysis to examine standard costs, actual costs, and cost control inside the organization. This study might also serve as a summary for other businesses looking to implement similar standards for effective management